2014
DOI: 10.3109/08990220.2014.923392
|View full text |Cite
|
Sign up to set email alerts
|

Phase-dependent modulation of corticospinal excitability during the observation of the initial phase of gait

Abstract: This study was undertaken to identify the temporal characteristics of corticospinal excitability of tibialis anterior muscle during the observation of the initial phase of gait. For this purpose, using transcranial magnetic stimulation, we recorded motor evoked potentials (MEPs) during the observation of the second step of an actor's first three steps of gait initiation with (complex gait) or without (normal gait) an obstacle and unstable surface. The results demonstrate that (1) MEPs during the observation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Our result is not in disagreement with this assumption, as the information flow direction (provided by our analysis) removes the afferent sensory component of the neural signaling and therefore considers only the direct contribute of specific motor areas to muscle activation. On the other hand, previous EMG studies examining reciprocal inhibition during gait already described the swing phase to be a critical event requiring supraspinal control (Lavoie et al, 1997) and TMS studies with lower limb muscles MEP recording found that the corticospinal tract is closely linked with the distal muscles controlling ankle flexion/extension during stepping (Schubert et al, 1999) and in particular with TA in the swing phase of the gait cycle (Capaday et al, 1999; Knikou et al, 2013; Takahashi et al, 2014). This is also compatible with previous works showing that in infants (Dominici et al, 2011) and elders (Stelmach and Hömberg, 1993) proximal muscle activity during walking exceeds distal muscle activity, whereas at intervening ages the reverse is true.…”
Section: Discussionmentioning
confidence: 99%
“…Our result is not in disagreement with this assumption, as the information flow direction (provided by our analysis) removes the afferent sensory component of the neural signaling and therefore considers only the direct contribute of specific motor areas to muscle activation. On the other hand, previous EMG studies examining reciprocal inhibition during gait already described the swing phase to be a critical event requiring supraspinal control (Lavoie et al, 1997) and TMS studies with lower limb muscles MEP recording found that the corticospinal tract is closely linked with the distal muscles controlling ankle flexion/extension during stepping (Schubert et al, 1999) and in particular with TA in the swing phase of the gait cycle (Capaday et al, 1999; Knikou et al, 2013; Takahashi et al, 2014). This is also compatible with previous works showing that in infants (Dominici et al, 2011) and elders (Stelmach and Hömberg, 1993) proximal muscle activity during walking exceeds distal muscle activity, whereas at intervening ages the reverse is true.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous EMG study of reciprocal inhibition during walking, the swing phase required greater control of cortical activation than the other gait phases ( Lavoie et al, 1997 ). In a transcranial magnetic stimulation study using lower extremity muscle motor-evoked potentials, the corticospinal tract was closely linked to muscles that control ankle flexion/extension during the swing phase of the gait cycle ( Takahashi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%